Newer approaches for optimal bioavailability of ocularly delivered drugs: Review - Kesavan K.; Balasubramaniam J.; Kant S.; Singh P.N.; Pandit J.K. (My University, 2025)
Eye diseases can cause discomfort and anxiety in patients, with the ultimate fear of loss of vision and facial disfigurement. Many regions of the eye are relatively inaccessible to systemically administered drugs and, as a result, topical drug delivery remains the preferred route in most cases. Drugs may be delivered to treat the precorneal region for conjunctivitis and blepharitis, or to provide intraocular diseases such as glaucoma, uveitis, and cytomegalovirus retinitis. Most of the ophthalmic formulation strategies aim at maximizing ocular drug permeability through prolongation of the drug residence time in the cornea and conjunctival sac, as well as minimizing precorneal drug loss. The conventional topical ocular drug delivery systems show drawbacks such as increased precorneal elimination and high variability in efficacy. Attempts have been made to overcome these problems and enhance ocular bioavailability by the development of newer drug delivery systems. This review is concerned with classification, recent findings and applications and biocompatibility of newer drug delivery systems for the treatment of ocular diseases. © 2011 Bentham Science Publishers Ltd.